What Does "Foreseeable" Mean? The Scope of Damages Under CISG Articles 74-77: Reasonability Principle of Foreseeability - We Don't Need a Crystal Ball - Ishida, Yasutoshi (Journal of Law and Commerce, 2022)
N/a